1986
DOI: 10.1007/bf00037131
|View full text |Cite
|
Sign up to set email alerts
|

Photooxidative reactions in chloroplast thylakoids. Evidence for a Fenton-type reaction promoted by superoxide or ascorbate

Abstract: A methyl viologen (MV)(*) mediated Mehler reaction was studied using Type C and D chloroplasts (thylakoids) from spinach. The extent of photooxidative reactions were measured as (a) rate of ethylene formation from methional oxidation indicating the production of oxygen radicals, and (b) rate of malondialdehyde (MDA) formation as a measure of lipid peroxidation. Without added ascorbate, 1 μM FerricEDTA increased ethylene formation by greater than 4-fold, but had no effect on MDA production. Ascorbate (1 mM) pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…Our former experiments showed that [OMIM]Cl may damage rice leaves and cause lipid peroxidation when applied at high concentrations which induced the increase of malondialdehyde (MDA) content [17]. Uphem [25] indicated that MDA would degrade chlorophyll. In this way the photosynthesis was affected by ILs and then the Hill reaction activity was decreased.…”
Section: Effects Of Ils On the Hill Reaction Activitymentioning
confidence: 99%
“…Our former experiments showed that [OMIM]Cl may damage rice leaves and cause lipid peroxidation when applied at high concentrations which induced the increase of malondialdehyde (MDA) content [17]. Uphem [25] indicated that MDA would degrade chlorophyll. In this way the photosynthesis was affected by ILs and then the Hill reaction activity was decreased.…”
Section: Effects Of Ils On the Hill Reaction Activitymentioning
confidence: 99%
“…9h–i), indicating that plant damage was becoming more severe. MDA not only has a cytotoxic effect by damaging cell membrane structure, but it can also degrade chlorophyll, thereby reducing plant photosynthesis [55]. The Chl content in this study decreased gradually, from 5.492 to 2.304 mg/g, as the duration of alkaline stress increased (Fig.…”
Section: Resultsmentioning
confidence: 63%
“…Because of these characteristics, H 2 O 2 is considered as a signaling molecule in growth and development [7], cell cycle [8], flowering [9], senescence [10] and in stress responses [11]. On the other hand, travelling H 2 O 2 may spread oxidative damage as the source of highly reactive hydroxyl radicals via Fenton chemistry [12] or direct photo-cleavage by UV-B [13]. Consequently, assessing H 2 O 2 concentrations in leaves is of special interest as indicator of physiological status and stress responses.…”
Section: Introductionmentioning
confidence: 99%